Keberadaan Pura Ulun Suwi Subak Tegal Pada Alih Fungsi Lahan Pertanian Di Kelurahan Kerobokan Kaja Kecamatan Kuta Utara Kabupaten Badung (Kajian Teo-Ekologi Hindu) - Gaduh, Acyutananda Wayan (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2020)
Hinduism teaches that nature is a manifestation of God. He is present and pervades all his creations. Today, Bali with most of itâ€™s Hindusm majority is also not spared from environmental damage. One of the phenomena that occurred was the conversion of agricultural land. The Balinese people who used to be known as agricultural societies are now threatened to lose their rice fields. The phenomenon of the conversion of agricultural land affects the existence of subak which is a traditional Balinese farmer organization based on religious socio-agrarian life. Subak which is a world cultural heritage is now facing a big challenge due to the reduced interest of Balinese people to become farmers and supported by the phenomenon of land conversion. Subak situation as above clearly affects the existence of Ulun Suwi temple as the center of the implementation of agricultural rituals conducted by subak.Based on the results of data processing obtained from field facts, found several factors that became the reason still survival Ulun Suwi Subak Tegal temple in the phenomenon of land conversion that occurred. Factors are: (1) internal factor such as religious factors and psychological factors, (2) external factor such as historical factors and cultural factors. The phenomenon of the conversion of agricultural land based on Hindu theological point of view can be seen from three domains: (1) a literary review, (2) the mythological review, and (3) based on the traditional view. While the implications of the conversion of agricultural land to the existence of Ulun Suwi temple are (1) the theological implications, (2) the social implications, and (3) environmental implications Â